Maintaining the Existence of Regional Languages in Lohiatala Village, Kairatu Barat District, West Seram Regency - Alfons, Christwyn Ruusniel; Titaley, Elsina; Pariela, Tonny Donald (Pascasarjana Universitas Mataram, 2024)
Maluku as an archipelago region contains cultural richness from various aspects by its indigenous people, especially local languages ​​which are a means of conveying thoughts and ideas. Local languages ​​themselves have institutionalized identity values ​​within the indigenous people who adhere to them because reality shows that the language in question confirms its origin. The difficulty is the inability of society to adapt to the development of globalization without ignoring regional languages ​​as local wisdom and identity. Of course this shows a shift to the point of language extinction, the existence of indigenous countries is also threatened due to the loss of identity as a marker of their identity. From the description of the reality of this indigenous community, strategic steps need to be taken, namely consolidating the local language (Alune) of Lohiatala Country which in the past was used to interact by ancestors into written form, this is because in the present it is generally unknown to the younger generation or school-age children. Furthermore, it is followed up by writing a dictionary of local language vocabulary so that it can be studied by the community today and in the future. This activity will be carried out through one of the Tridharma of higher education, namely Community Service with a verification method (confirmation of the writing of the definition of the local language per vocabulary accompanied by its meaning in Indonesian) against the results of the search that has been carried out in 2023, and the publication of the dictionary book